Penerapan Metode Double Loop Problem Solving dengan Berbantuan Media Aplikasi Animaker dalam Pembelajaran Menulis Teks Anekdot pada Siswa Kelas X SMA Pasundan 2 Bandung Tahun Pelajaran 2023/2024 - Dewi Banowati Arbaini; Titin Nurhayatin; Rendy Tiandy (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2024)
This research was conducted to overcome problems among students who still have difficulties in writing skills, especially in learning to write anecdotal texts. The causal factor is that educators are less varied in choosing learning methods and media. The aim of this research is to test the ability of writers and students in learning to write anecdotal texts using the Double Loop Problem Solving Method with the help of the Animaker Application media. The research method used was a Quasi Experimental method with a Nonequivalent control group design type. Data collection techniques include literature review, trials, observation, tests and documentation. Based on the research results, it shows that students are able to write anecdotal texts well based on content, structure and linguistic rules. This is supported by the average pre-test score in the experimental class of 56.4 and the average post-test score of 80.2, so there is an increase of 23.8. Referring to the results of statistical calculations using Mann Whitney, it shows that there is a significant difference in the ability of students in writing anecdotal texts in the experimental class which uses the Double Loop Problem Solving method assisted by media Animaker application with the ability of students in the control class which uses the method discution. This is supported by the Asymp Sig results. (2-tailed) 0.00 < 0.05. Based on these data, it can be concluded that learning anecdotal texts using the Double Loop Problem Solving method assisted by the Animaker application is effective in improving students' ability to write anecdotal texts.